Boys don't cry: Trauma, trauma narrative and masculine practice among young male who engaged in harmful sexual behaviour. Issue 1 (12th January 2023) - Zaniewski, Bartosz; Dallos, Rudi; Stedmon, Jacqui; Welbourne, Penelope
Compelling evidence suggests that majority of young men who engaged in harmful sexual behaviour (HSB) were subjected to various forms of trauma and adverse childhood experiences. This research explores lived experience of a group of young men who engaged in HSB, what sense they made of it and how their positioned themselves towards these events including HSB, so they are able to maintain their self-integrity. It also explores impact of lived experience with consideration for broader family and cultural discourses. Transition to Adulthood Attachment Interview and Semi-structured interview were employed and Dynamic- Maturation Model of attachment were utilised for this research since it differentiates for dismissed and pre-occupied trauma spectrums. Findings highlighted that all of the young men presented mainly with complex unresolved dismissed trauma or loss and some with both types of trauma. Furthermore, they employed dominant hegemonic culturally shared discourses of masculinity to make sense of their lived experience. The ways in which experiences of trauma shaped the HSB pathway that developed is discussed.